Model Pembelajaran PBL untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Kemampuan dan Keterbatasanku di Kelas VII SMPN 10 Singkawang - Marina Yuli (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims about the lower of study result in Religion Education of 7th grade in SMPN 10 Singkawang about My ability and limitless. This case causes of the ability of religion teacher could not stimulus the manner of students studying in the classroom until they can not develop their creativity and critical thinking of them. Beside that, it still use speech and simple discussion that make the lesson progress useless. This result implies bad result of their achievement of learning. In the other words, their results become lower and does not fit with their target. This research aims is to know the result of students learning achievement about Religion Education of 7th grade in SMPN 10 Singkawang. The methods of this research about Problem Based Learning and to develop learning strategy of students. This research instrument using Class researching that had done into 2 steps. The data resources from students study result and students exam paper. In this research had done before using Problem Based Learning, from the 9 students, we can find the weakness result of study progress about 67%, the result of pass for this material is about 33%. After the hypothesis and evaluation of the first period using problem based learning, the number of students who could pass the evaluation is 78% and 22 % get fail of this evaluation. The high increase could be found in the 2nd period, that both of this period about 100%. In this case, we can conclude that there are progressing begin from the 1st and the 2nd periods. It is cause of problem Based Learning methods in the classroom.